Recruitment and selection practices of organizations in Malaysia - Fidelis Awing, James Nichol (Universiti Malaysia Sarawak (UNIMAS), 2019)
The main purpose of this study is to study and investigate the recruitment and selection practices of organizations in Malaysia. The focus of this particular project was to assess the recruitment and selection activities of organizations in Malaysia. It will also discuss on the the organization's current method for recruitment and selection activities. It showed that majority the organization implemented online recruitment. It will also discuss on the issues encounter by the organization regarding the recruitment and selection activities. The issues occurred due to the poor of recruitment and selection process. This study is a qualitative research. There were 3 informants from different organizations involved in this study which are from production, retail and petroleum company. Apart from that, the discussion and past studies regarding this topic was also discussed. Lastly, the summary of all chapters, recommendation for organization, human resource practitioner and future research, and limitation of this study also been discussed.